A phase I study of farletuzumab, a humanized anti-folate receptor α monoclonal antibody, in patients with solid tumors - Sasaki, Yasutsuna (Invest New Drugs, 2014)
Farletuzumab is a humanized monoclonal antibody against folate receptor α (FRA). The purpose of the study is to assess safety and tolerability, the pharmacokinetic (PK) profile, and preliminary antitumor effect. Patients with ovarian cancer (OC) or FRA-expressing solid tumors who are resistant to standard treatments were eligible for the study. After single-dose administration for PK assessment, farletuzumab was administered by intravenous injection, repeating every week until disease progression. Dose-limiting toxicities (DLTs) were defined as grade 4 hematological and grade 3/4 nonhematological toxicities. Dose escalation was planned in 4 cohorts (50, 100, 200, and 400 mg/m(2)). Fourteen patients with OC and two patients with gastric cancer (GC) received farletuzumab infusion. Neither DLTs nor grade 3/4 toxicities were reported in all cohorts. Major adverse events, including grade 1/2 infusion related reaction (15 patients, 93.8 %), headache (seven patients, 43.8 %), and nausea and decreased appetite (five patients each, 31.3 %), were observed and medically managed. AUC and C(max) increased dose-dependently and linear PK profiles were observed. No tumor shrinkage was recorded, but long-term disease stabilization for 25 and 20 months was observed in one patient with clear cell OC (100 mg/m(2)) and one patient with GC (400 mg/m(2)), respectively. No cumulative toxicity occurred in any patient. Farletuzumab was well tolerated in Japanese patients with a similar PK profile as compared with the US population. Long-term disease stabilization was observed in a subpopulation of clear cell OC and GC; both of them were resistant and progressive after standard chemotherapies (ClinicalTrials.gov Identifier: NCT01049061).